Innovation and Technology in Arabic Language Learning in Indonesia: Trends and Implications - Ibnu Fitrianto (International Journal of Post Axial: Futuristic Teaching and Learning, 2024)
This study investigates the role of technological innovations in Arabic language education in Indonesia, focusing on the adoption of digital tools and innovative teaching methods. The research examines the current trends in the use of mobile applications, e-learning platforms, and social media, as well as the implementation of methods such as flipped classrooms, gamification, and collaborative online learning. Data were collected from various educational institutions to assess the impact of these technologies on student engagement, motivation, and language proficiency. The findings reveal that while technological integration has significantly enhanced the learning experience and accessibility of Arabic language education, it also presents challenges, including digital infrastructure limitations, teacher preparedness, and potential disparities in access among students. This study highlights the need for targeted interventions, such as comprehensive teacher training and infrastructure development, to maximize the benefits of technology in Arabic language learning. The research contributes to the growing body of literature on the intersection of language education and technology, offering insights for educators, policymakers, and stakeholders aiming to improve Arabic language instruction in Indonesia